Ethnic‐specificity, evolution origin and deleteriousness of Asian BRCA variation revealed by over 7500 BRCA variants derived from Asian population. Issue 6 (30th November 2022) - Qin, Zixin; Li, Jiaheng; Tam, Benjamin; Sinha, Siddharth; Zhao, Bojin; Bhaskaran, Shanmuga Priya; Huang, Teng; Wu, Xiaobing; Chian, Jia Sheng; Guo, Maoni; Kou, Si Hoi; Lei, Huijun; et al.
Abstract: Pathogenic variation in BRCA1 and BRCA2 ( BRCA ) causes high risk of breast and ovarian cancer, and BRCA variation data are important markers for BRCA ‐related clinical cancer applications. However, comprehensive BRCA variation data are lacking from the Asian population despite its large population size, heterogenous genetic background and diversified living environment across the Asia continent. We performed a systematic study on BRCA variation in Asian population including extensive data mining, standardization, annotation and characterization. We identified 7587 BRCA variants from 685 592 Asian individuals in 40 Asia countries and regions, including 1762 clinically actionable pathogenic variants and 4915 functionally unknown variants (https://genemutation.fhs.um.edu.mo/Asian-BRCA/ ). We observed the highly ethnic‐specific nature of Asian BRCA variants between Asian and non‐Asian populations and within Asian populations, highlighting that the current European descendant population‐based BRCA data is inadequate to reflect BRCA variation in the Asian population. We also provided archeological evidence for the evolutionary origin and arising time of Asian BRCA variation. We further provided structural‐based evidence for the deleterious variants enriched within the functionally unknown Asian BRCA variants. The data from our study provide a current view of BRCA variation in the Asian population and a rich resource to guide clinical applications of BRCA ‐related cancer for the Asian population. Abstract : What's new? Pathogenic variation in BRCA increases the risk of breast and ovarian cancer. However, BRCA variation in the Asian population remains poorly characterized. This systematic analysis identified 7587 BRCA variants from 685 592 Asian individuals in 40 Asian regions, including 1762 clinically actionable pathogenic variants, and revealed the highly ethnic‐specific nature of Asian BRCA variation. Moreover, the authors provide archeological evidence for the evolutionary origin and arising time of Asian BRCA variation and protein structure‐based evidence for the enrichment of deleterious variants in the abundant unclassified BRCA variants. The data provide a rich resource to guide clinical applications in the Asian population.